Extraction of pharmacologically active thymoquinone in nigella sativa L. - Nazeri, Nasaruddin (2006)
Black Seed Oil or Nigella Sativa L. is said to be the universal remedy. It has an amazing healing power and its greatness has been recorded in the Hadith stating that it could cure any diseases except death. Today black seed oil has been commercialized; research is carried out from time to time to improve its quality. This research purposely is to determine the best solvent to be used in extracting black seed oil, in terms of time and most importantly its yield. Rotary Evaporator employed with Ultra Sonic Bath is used in extraction process. Time and heat is chosen as the parameter to manipulate and several trials is carried out. Optimum condition will be recognized. After the extraction, oil is obtained then HPLC analysis is carried out to determine the existence of Thymoquinone which is the main compound in Black Seed Oil. Quantitatively, more Thymoquinone means better quality of Black Seed Oil.